1998
DOI: 10.1086/306032
|View full text |Cite
|
Sign up to set email alerts
|

Abundances of HCN and HNC in Dark Cloud Cores

Abstract: We have determined the abundances of HCN and HNC toward 19 nearby dark cloud cores by observations of optically thin H13CN (J \ 1È0) and HN13C (J \ 1È0) lines. The column density of HCN is found to be correlated with that of HNC. The abundance ratio of [HNC]/[HCN] is determined to be 0.54È4.5 in the observed dark cloud cores. These results are consistent with the idea that HCN and HNC are produced mainly by a recombination reaction of HCNH`with electrons in dark cloud cores. Furthermore, the [HNC]/[HCN] ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
239
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(271 citation statements)
references
References 43 publications
29
239
3
Order By: Relevance
“…From the abundance ratios of HNC, HCO + , and HCN for each IRDC in Table 4, we find that HNC is more abundant than HCO + and HCN, except for IRDC G331.035-00.418, which agree with the fact that HNC molecule is the tracer of the cold gas. And the derived NHNC/NHCN = 1.47 ± 0.50 is consistent with the results in the dark cloud cores (Hirota et al 1998). NHCN/N HCO + is approximately equal to 1, implying the similar origin and chemistry evolution of these two molecules.…”
Section: 32supporting
confidence: 88%
See 1 more Smart Citation
“…From the abundance ratios of HNC, HCO + , and HCN for each IRDC in Table 4, we find that HNC is more abundant than HCO + and HCN, except for IRDC G331.035-00.418, which agree with the fact that HNC molecule is the tracer of the cold gas. And the derived NHNC/NHCN = 1.47 ± 0.50 is consistent with the results in the dark cloud cores (Hirota et al 1998). NHCN/N HCO + is approximately equal to 1, implying the similar origin and chemistry evolution of these two molecules.…”
Section: 32supporting
confidence: 88%
“…N2H + was more resistant to freeze-out on grains than the carbon-bearing species (Bergin et al 2001). HNC was particularly prevalent in cold gas (Hirota et al 1998). HCO + often showed infall signatures and outflow wings (Rawlings et al 2004;Fuller et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In their study, they used the rotational excitation rate constants for HCN with He calculated by Green & Thaddeus (1974) to deduce the rate constants for the rotational excitation of HCN by H 2 , assuming that the values for HNC-He and HNC-H 2 collisions were identical to the HCN ones. (Hirota et al 1998) performed detailed HCN and HNC observations in various dense molecular clouds leading to similar results for TMC-1 to (Pratap et al 1997) despite the lower abundances derived from Hirota et al. Taking into account the various detection uncertainties, the simulated HCN abundance is compatible with a cloud age between 310 5 yr and 610 5 yr varying from (2-6)10 -8 relative to H 2 .…”
Section: Comparison With Observationsmentioning
confidence: 58%
“…(Dickens et al 2000) found higher HCN and HNC densities attributing their differences with (Swade 1989) to the optical depth estimation as Swade assumed optically thin emission, potentially underestimating the column densities. (Hirota et al 1998) were not able to evaluate the HNC abundance and therefore only reported HCN abundances. Recently (Hily-Blant et al 2010) determined CN, HCN and HNC abundances in various starless cores.…”
Section: Comparison With Observationsmentioning
confidence: 99%
See 1 more Smart Citation